Effect of d122n mutation in bak1 on structural integrity of protein complex consisting Haesa, Ida and bak1 Ectodomain- an in-silico study - Kinnori, Kuhu (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.